1997
DOI: 10.1677/joe.0.1540113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence suggesting that cadmium induces a non-thyroidal illness syndrome in the rat

Abstract: The effect of in vivo administration of cadmium chloride on the pituitary-thyroidal axis was assessed in 200 g body weight Wistar rats. A dose of 2.5 mg/kg body weight was injected i.v. 24 h before the experiments were initiated. Plasma thyroxine (T4) and tri-iodothyronine (T3) concentrations in cadmium-treated rats were significantly (P < 0.01) decreased, whereas plasma TSH failed to increase in response to low T4 and T3. However, the TSH response to TRH and the pituitary content of TSH in these rats were bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
1
5
1
Order By: Relevance
“…The supply of thiol groups can protect enzymes from toxic effects of metals other than cadmium (Susuki and Osaki 1984). However, this and previous data suggest that factors other than thiol groups may be involved in T 4 deiodination, since the addition of DTT to cadmium-treated homogenates did not fully restore the levels of deiodination observed in cadmium-free homogenates in this and previous work (Paier et al 1993;Yoshida et al 1987;Pavia et al 1997). Similar conclusions were suggested by Harris et al (1979) and Chopra (1980) after studying the role of sulfhydryl groups on T 4 to T 3 conversion in rat liver homogenates.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…The supply of thiol groups can protect enzymes from toxic effects of metals other than cadmium (Susuki and Osaki 1984). However, this and previous data suggest that factors other than thiol groups may be involved in T 4 deiodination, since the addition of DTT to cadmium-treated homogenates did not fully restore the levels of deiodination observed in cadmium-free homogenates in this and previous work (Paier et al 1993;Yoshida et al 1987;Pavia et al 1997). Similar conclusions were suggested by Harris et al (1979) and Chopra (1980) after studying the role of sulfhydryl groups on T 4 to T 3 conversion in rat liver homogenates.…”
Section: Resultscontrasting
confidence: 69%
“…This study used cadmium concentrations similar to those which in liver (Yoshida et al 1987;Paier et al 1993) and the pituitary gland (Pavia et al 1997) significantly inhibited T 4 deiodination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AgNPs may alter the mitochondrial function of the thyroid epithelial cells, which might reduce cellular ATP production required as an energy source for synthesis and release of thyroid hormone [27]. It has been reported that AgNPs induced mitochondrial dysfunction and activated the caspase-3 that may consequently directed the cell toward mitochondrial-dependent apoptosis [29]. However, other study disagreed with our finding, where they found that daily exposure of animals to different doses (20, 50 and 150 mg/kg) of iron oxide NPs for 15 consecutive days resulted in a significant increase in the serum levels of T4, accompanied by significant reduction in TSH serum levels [30].This can be explained by the ability of the absorbed NPs to circulate with blood and passed to accumulate within different organs including thyroid tissue as their distribution was known to be size dependent [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This chromatographic technique allowed a reliable assessment of the percentage distribution of the radioactive compounds generated during the incubation of labeled T4 (15,16). The absolute amount of [ …”
Section: Deiodination Studiesmentioning
confidence: 99%